Peace Channel: A channel for human rights education and peace in Nagaland (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
Nagas are a group of tribes of Southeast Asian origins culturally distinct from the Indo-Aryan cultural mainstream. They live in relative independence from one another scattered over large tracts of hills in the Northeastern region of India adjoining Myanmar. Naga tribes in the present state of Nagaland became part of India only after Indian independence in 1947 – a case which is still contested by armed Naga nationalist groups who also simultaneously declared independence and run a parallel underground government throughout Naga inhabited areas. According to 2001 Census 19,88,639 Naga population live in Nagaland state with an area of 16,579 sqkm. The state is situated between 93°20'E and 95°15' E and between 25°6' and 27°4' N. The state has common boundaries with Myanmar in the East, Assam in the West; Arunachal Pradesh and a part of Assam in the North with Manipur in the south. Nagaland is home to 16 major tribes who are known for their own distinct character and identify of each tribe in terms of Tradition, custom, language and attire. About 90% of the state’s population is Christian and there are a good many number of churches located in all parts of the state. For this reason Nagaland is popularly known as the “most Baptist state in the world’. Christianity began to set food among the Naga tribes in1839; by 1930 there were 60,000 members in several Churches.